Conscious Experience and Episodic Memory: Hippocampus at the Crossroads - Behrendt, Ralf-Peter (Frontiers in Psychology, 2013)
If an instance of conscious experience of the seemingly objective world around us could be regarded as a newly formed event memory, much as an instance of mental imagery has the content of a retrieved event memory, and if, therefore, the stream of conscious experience could be seen as evidence for ongoing formation of event memories that are linked into episodic memory sequences, then unitary conscious experience could be defined as a symbolic representation of the pattern of hippocampal neuronal firing that encodes an event memory – a theoretical stance that may shed light into the mind-body and binding problems in consciousness research. Exceedingly detailed symbols that describe patterns of activity rapidly self-organizing, at each cycle of the θ rhythm, in the hippocampus are instances of unitary conscious experience that jointly constitute the stream of consciousness. Integrating object information (derived from the ventral visual stream and orbitofrontal cortex) with contextual emotional information (from the anterior insula) and spatial environmental information (from the dorsal visual stream), the hippocampus rapidly forms event codes that have the informational content of objects embedded in an emotional and spatiotemporally extending context. Event codes, formed in the CA3-dentate network for the purpose of their memorization, are not only contextualized but also allocentric representations, similarly to conscious experiences of events and objects situated in a seemingly objective and observer-independent framework of phenomenal space and time. Conscious perception is likely to be related to more fleeting and seemingly internal forms of conscious experience, such as autobiographical memory recall, mental imagery, including goal anticipation, and to other forms of externalized conscious experience, namely dreaming and hallucinations; and evidence pointing to an important contribution of the hippocampus to these conscious phenomena will be reviewed.